KORTES Mission for Solar Activity Monitoring Onboard International Space Station - Kirichenko, Alexey; Kuzin, Sergey; Shestov, Sergey; Ulyanov, Artem; Pertsov, Andrey; Bogachev, Sergey; Reva, Anton; Loboda, Ivan; Vishnyakov, Eugene; Dyatkov, Sergey; Erkhova, Nataliya; Stȩślicki, Marek; et al. (Frontiers in Astronomy and Space Sciences, 2021)
We present a description of the recent advances in the development of the KORTES assembly -- the first solar oriented mission designed for the Russian segment of International Space Station. The KORTES consists of several imaging and spectroscopic instruments collectively covering a wide spectral range extending from extreme ultraviolet (EUV) wavelengths to X-rays. The EUV telescopes inside KORTES will trace the origination and dynamics of various solar phenomena, e.g. flares, CMEs, eruptions etc. EUV spectra provided by grazing-incidence spectroheliographs will enable precise DEM-diagnostics during these events. The monochromatic X-ray imager will observe the formation of hot plasma in active regions and outside them. The SolpeX module inside KORTES will offer an opportunity to measure fluxes, Doppler shifts and polarization of soft X-ray emission both in lines and continuum. SolpeX observations will contribute to studies of particle beams and chromospheric evaporation. The instrumentation of KORTES will employ a variety of novel multilayer and crystal optics to be discussed. The deployment of KORTES is planned of 2024.